Surgical Periodontal Management of Peripheral Ossifying Fibroma: A Series of Three Cases - Karo Parsegian; Roger M. Arce; Nikola Angelov (Case Reports in Dentistry)
Peripheral ossifying fibroma (POF) is a benign swelling of the gingival connective tissue commonly associated with dental biofilm and biofilm-retentive dental appliances. In the present case report, we described three cases of POF with different clinical presentations and treatment approaches. The treatment consisted of the removal of supra- and subgingival calculus, followed by a flap surgery with excision of the entire lesion ensuring the inclusion of the periosteal bed. The first patient developed POF during her pregnancy that remained clinically noticeable postpartum. The second case represented a rare case of POF appearing on the palatal aspect of the anterior maxilla of an African American male. The third case represented POF that developed on the mandible, and contrary to the first two cases, it was excised using a diode laser and not a scalpel blade. All patients showed uneventful healing during follow-up appointments; however, poor patient compliance did not allow for evaluation of long-term healing responses and possible recurrence of the lesion. Within the limitations of this clinical report, it is evident that the periodontal surgical approach was effective in managing POF with stable short-term clinical outcomes.